Pendidikan Karakter dalam Novel Negeri 5 Menara Karya Ahmad Fuadi dan Novel Laskar Pelangi Karya Andrea Hirata: Tinjauan Sosiologi Sastra - Yulia Fitrina; Atmazaki .; Harris Effendi Thahar (Fakultas Bahasa dan Seni UNP, 2013)
Abstract: Character Building is a concept in the world of education related to planting noble values ​​and moral values ​​to students that are expected to produce students who are not only smart intellectually, but also smart emotionally and spiritually. Character building can be found in two literary novels “Laskar Pelangi” by Andrea Hirata and “Negeri 5 Menara” by Ahmad Fuadi, which will be analyzed through the perspective of sociology of literature. Character building in both novel will apply a grand design developed by Kemendiknas (2010) that divided it into five points, they are: the character building that related to the God, individual, humans, environment and nationhood. Then, the character building in both novels will be discussed in the form of knowing the good, feeling the good, and acting the good. Kata Kunci: pendidikan karakter, novel Negeri 5 Negara, novel Laskar Pelangi